2021
DOI: 10.3390/ijerph18062837
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Adherence, Body Composition and Performance in Beach Handball Players: A Cross Sectional Study

Abstract: Background: Beach handball (BH) is a sport in which sporting performance is influenced, together with team interaction, by individual performance in terms of strength. Body composition is one of the main factors for sports performance and eating habits can condition this variable. The Mediterranean diet (MD) can significantly reduce the risk of mortality or cardiovascular disease. In addition, the Spanish Ministry of Agriculture, Food and Environment carries out different campaigns to promote it among young at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 56 publications
(30 reference statements)
6
24
0
Order By: Relevance
“…The same occurred with the variable of musculoskeletal fitness of the upper extremities, measured by Handgrip since the senior players had shown higher values (p = 0.015). This coincides with previous research conducted with other samples of handball players [25,45]. It seems that the reasons, as demonstrated in female volleyball players [46], are that these differences may be directly related to neuromechanical adaptations because of the repeated actions taking place in training and matches.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The same occurred with the variable of musculoskeletal fitness of the upper extremities, measured by Handgrip since the senior players had shown higher values (p = 0.015). This coincides with previous research conducted with other samples of handball players [25,45]. It seems that the reasons, as demonstrated in female volleyball players [46], are that these differences may be directly related to neuromechanical adaptations because of the repeated actions taking place in training and matches.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that the KIDMED measures the quality of the diet in terms of adherence to the Mediterranean diet; however, it is not able to measure the amount of food eaten by the players. As previously observed [25], adherence to the Mediterranean diet in female beach handball players is moderate.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…that make it an intermittent high intensity contact sport [3,4]. The different playing positions are goalkeepers, wings, specialist, pivots, and defenders [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have shown that optimal body composition in athletes is associated with improvements in physical performance (aerobic and anaerobic) and muscle strength [21][22][23][24][25][26]. For optimal performance of BH players, it is necessary that their weight and fat percentage are within the recommended parameters for their age group, position, and sex [6,9].…”
Section: Introductionmentioning
confidence: 99%